Mathematical Modelling of the Price Range in the Procurement of Ferrous Scrap by Metallurgical Enterprises - Ivanova, Tatyana Aleksandrovna; Trofimova, Violetta Shamilyevna; Kalitaev, A.N.; Stepanov, Dmitry Gennadyevich (Economy of Regions, 2018)
For metallurgical enterprises, it is important to understand the limits of the most probable values of prices and geographical area for procurement of ferrous scrap in the regions. In order to define the maximal scrap prices in the regions, the authors have developed a mathematical model of “auction purchases”. This model equally assesses price competition between scrap consumers. When setting the price, we consider the territorial imbalances between scrap supply and demand in the regions; costs for scrap transportation from supplier to consumer; price level for scrap in the “windows for exports”. We calculate the lowest price according to the “export parity”. Пє results of the calculations allow evaluating a range of regional prices and interregional flows of scrap. Wis approach is unnown in the published works of Russian and foreign researchers. For calculations, we have developed a special software. We following initial data were used: data on railroad transportation of ferrous scrap in the Russian Federation provided by JSC Russian Railways; handbooks of railway tariffs 10-01 between railway stations of the Russian Federation; statistical data on prices of 3A metal scrap in the “windows for exports”. We article presents the formal structure of the model of “auction procurement”, the algorithm of its implementation and the results of calculations. We price level calculated according to the model of “auction procurement” can be used in management practice as potentially highest level of price, which can be reached in the conditions of competition between consumers of scrap in a situation when the negotiations are impossible. We proposed mathematical model allows a metallurgical enterprise to prove and implement a differentiated approach to the formation of regional prices of scrap, and to define regions for scrap purchasing.